1943
DOI: 10.1128/jb.46.5.399-403.1943
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the Rôle of Niacin and Thiamine in the Metabolism of Glucose by Staphylococcus aureus

Abstract: In a study on the inhibitive effect of glucose, in media devoid of niacin, on the growth of bacteria requiring this vitamin for carbohydrate metabolism, it was noted that there exists a certain coordination between niacin and thiamine in the utilization of glucose by staphylococci. The experiments reported below were designed to elucidate the specific r6les of these two vitamins in the carbohydrate metabolism of these organisms.Knight, in 1937, was the first to demonstrate that Staphylococcus aureus can grow i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1944
1944
1966
1966

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…If the assumption is made that the organisms separated from the peritoneal and thoracic exudates had the opportunity to possess more thiamine and nicotinamide than the organisms grown in vitro, then the striking difference in glucose metabolism is more easily understood. Kligler, Gossowicz and Bergner (1943) showed that nicotinamide and thiamine had a definite effect on the glucose metabolism of S. aureus. Thiamine, which catalyzes many reactions involved in the breakdown of pyruvic acid, had no effect on the anaerobic glycolytic reaction.…”
Section: Globulin Fractiontmentioning
confidence: 99%
“…If the assumption is made that the organisms separated from the peritoneal and thoracic exudates had the opportunity to possess more thiamine and nicotinamide than the organisms grown in vitro, then the striking difference in glucose metabolism is more easily understood. Kligler, Gossowicz and Bergner (1943) showed that nicotinamide and thiamine had a definite effect on the glucose metabolism of S. aureus. Thiamine, which catalyzes many reactions involved in the breakdown of pyruvic acid, had no effect on the anaerobic glycolytic reaction.…”
Section: Globulin Fractiontmentioning
confidence: 99%
“…However, most of the recent data in support of this view are general rather than specific in character. Kligler et al (148,149) reported that nicotinic acid and thiamine are required if glucose is present in the medium, but not if it is absent. Many papers have been published showing that thiamine (119,(321)(322)(323)358, 360, 365); riboflavin (2, 143), pantothenic acid (26, 78, 120), and nicotinic acid (or coenzyme I) (82, 211) increase respiration (oxygen uptake, carbon dioxide production or methylene blue reduction) by cells (e.g., Staphylococcus aureus, Propionibacterium pentosaceum, Proteus morganii, Lactobacillus mannitopoeus, dysentery bacilli, Hemophilus parainfluenzae) acting on various substrates (e.g., glucose, lactate, pyruvate).…”
Section: Function Of Growth Factorsmentioning
confidence: 99%